Effect of Difference of Two Blended Learning Styles across the Web (Individual /Collective) on Developing Programming Skills for Secondary School Students - Abdelraouf Mohamed Ismail,; Basmah Abdulkareem Alshammari, (المجلة الدولية للحاسبات والمعلوماتية, 2024)
The study aimed to learn the effect of the differently integrated web learning (individual/group) learning on the development of web page design skills for high school students, and the current study used the method of experimental, and the study sample consisted of (20) students from the first secondary school students, I also used the two -settling experimental design; Where the study of the first experimental group according to the web learning in the individual style and the second group was studied according to the web learning in the collective style; And to the existence of statistically significant differences at the level of significance 0.05) ≥ α) between the averages of the two experimental groups in the post -application in the skill test in favor of the experimental group that uses integrated learning across the web in its individual style, which confirms that the individual integrated learning outperformed the collective learning in the development of The cognitive and skill aspect assigned to the design of web pages. The study recommended attention in providing technical equipment in schools to turn from its traditional form to electronic, training teachers in schools to develop their skills in the use of modern digital applications and urge them to do them in the educational process, and to employ integrated learning in the classroom.